2016
DOI: 10.1155/2016/2647865
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic Risk in Hyperlipidemic Men and Women

Abstract: Objective. The aim of this study was to evaluate sex specific differences of metabolic and clinical characteristics of treated hyperlipidemic men and women (HL-men and HL-women). Methods. In this study vascular and metabolic characteristics of 35 HL-women and 64 HL-men were assessed. In addition a sex specific analysis of metabolic and nutritional habits of HL-patients with prediabetes (HL-IGR) was done. Results. HL-women were older and had favourable concentrations of high density lipoprotein cholesterol (HDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…23 Michael Leutner et al showed in their study that there was no significant difference in carotid IMT measurements between Hyperlipidemic men and Hyperlipidemic women. 24 In current study we found that stroke is associated with increased IMT. Similar to this study Peiyang Zhou et al stated that there is a link between IMT and the risk of stroke in young people.…”
Section: Discussionsupporting
confidence: 49%
“…23 Michael Leutner et al showed in their study that there was no significant difference in carotid IMT measurements between Hyperlipidemic men and Hyperlipidemic women. 24 In current study we found that stroke is associated with increased IMT. Similar to this study Peiyang Zhou et al stated that there is a link between IMT and the risk of stroke in young people.…”
Section: Discussionsupporting
confidence: 49%
“…Obesity is a growing epidemic and patients characterized as obese are at risk for developing cardiovascular complications that could be linked to 3.4 million deaths worldwide in 2010 [21]. High fat and high cholesterol diets found in Western countries contribute to the development of cardiovascular risk factors such as hyperlipidemia and hypercholesterolemia [8]. High levels of these circulating lipids can lead to the accumulation of lipid plaques in arterial walls, which are also known as atherosclerosis [22].…”
Section: Importance Of Lipids In the Development Of Cardiovascular Diseasementioning
confidence: 99%
“…Therefore, lipids have a direct role in cardiovascular function. On the other hand, regarding lipid excess experienced when diets high in fat are consumed, hyperlipidemia and hypercholesterolemia can result, which puts patients at risk for developing atherosclerosis and cardiometabolic disease [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies have found that men have a higher risk of cardiovascular mortality compared to women and have a higher risk of developing CVD at earlier onset (Leutner et al, 2016). Previous twin studies on common CVD risk factors have also established that genetic and environmental factors contributing to them often differ by sex, age, and ethnicity (Li et al, 2016;Liao et al, 2017;Poveda et al, 2017;Song et al, 2015;Tanaka et al, 2015).…”
mentioning
confidence: 99%